Mechanism study and theoretical simulation on heat split phenomenon in dual-cooled annular fuel element. (August 2016) - Deng, Yangbin; Wu, Yingwei; Li, Yuanming; Zhang, Dalin; Tian, Wenxi; Su, G.H.; Qiu, Suizheng
Highlights: The mechanism study on heat split was carried out. A thermal–mechanical behavior analysis code FROBA-ANNULAR was introduced. The simulation on heat split was performed by FROBA-ANNULAR code. The influence of heat split on asymmetric heat transfer and DNBR was analyzed. Abstract: In this study, the mechanisms that cause heat split, a specific phenomenon in dual-cooled annular fuel elements, were investigated. On the basis of thermal resistance analysis, the developing process of heat split phenomenon was summarized. It was found that thermal expansion, fuel densification, swelling, creep, relocation and fission gas release are the original parameters driving the development of heat split. Due to these factors, thermal resistances for heat flux to internal and external channels change with the operating time, which results in heat split. Furthermore, the theoretical simulation on heat split was performed by FROBA-ANNULAR, which is a coupled thermal–mechanical analysis code for dual-cooled annular fuel elements. Key parameters at different burnup stages, including gap size, gap conductance, temperature profile, coolant flux and heat flux were obtained. The calculation result shows that the fraction of heat flux to the internal cooling channel experiences complicated variation at the range of 32.9–39.7%. In addition, it was found that heat split does not match with the coolant split, especially at the lower burnup stage. Asymmetric heat transfer occurred because of the imbalance between heat split and coolant split, resulting in a substantial asymmetric temperature profile. Furthermore, heat split exerts an influence on DBNRs of inner and outer channels, although the computational values were still within the allowable limits.